IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society 2014
DOI: 10.1109/iecon.2014.7049033
|View full text |Cite
|
Sign up to set email alerts
|

The scheme of a novel methodology for zonal division based on power transfer distribution factors

Abstract: Abstract-One of the methodologies that carry out the division of the electrical grid into zones is based on the aggregation of nodes characterized by similar Power Transfer Distribution Factors (PTDFs). Here, we point out that satisfactory clustering algorithm should take into account two aspects. First, nodes of similar impact on cross-border lines should be grouped together. Second, cross-border power flows should be relatively insensitive to differences between real and assumed Generation Shift Key matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Further algorithms based on LMPs are applied in (Wawrzyniak et al, 2013;Imran and Bialek, 2008). In contrast to the LMP-based methodology, cluster algorithms based on PTDFs are applied by (Bergh et al, 2016;Sarfati et al, 2015;Klos et al, 2014;Kang et al, 2013;Wawrzyniak et al, 2013;Duthaler et al, 2012). (Bergh et al, 2016) also investigate improved PZCs for CWE and Italy, Czech Republic and Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further algorithms based on LMPs are applied in (Wawrzyniak et al, 2013;Imran and Bialek, 2008). In contrast to the LMP-based methodology, cluster algorithms based on PTDFs are applied by (Bergh et al, 2016;Sarfati et al, 2015;Klos et al, 2014;Kang et al, 2013;Wawrzyniak et al, 2013;Duthaler et al, 2012). (Bergh et al, 2016) also investigate improved PZCs for CWE and Italy, Czech Republic and Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to the LMP-method (Duthaler, 2012), (Kang et al, 2013), (Klos et al, 2014), (Kłos et al, 2015), (Sarfati et al, 2015) and (Bergh et al, 2016) apply cluster algorithms based on PTDF-values. (Kłos et al, 2015) aim to reduce loop effects by clustering PTDF values.…”
Section: Investigate Zonal Solutions Based Onmentioning
confidence: 99%
“…The authors cluster PTDF values on selected critical branches and, after investigating a base scenario, analyse several delimitations with different amounts of price zones. (Klos et al, 2014) identify critical branches using a clustering based on KKT-multipliers first and cluster PTDFvalues afterwards. (Kang et al, 2013) investigate the IEEE-39 system for a given number of zones.…”
Section: Investigate Zonal Solutions Based Onmentioning
confidence: 99%
“…Yet studies have also shown the substantial effects of congestion management and have reported more frequent zero and negative prices in the more peripherical northern areas of Germany. With regard to our investigation, the considered studies essentially deal with two aspects: the computation of robust configurations with different cluster algorithms (Burstedde 2012;Kang et al 2013;Breuer and Moser 2014;Klos et al 2014) and the analysis of the system's effects with exogenously given bidding zones (Trepper et al 2015;Egerer et al 2016;Blume-Werry et al 2017).…”
Section: Introductionmentioning
confidence: 99%